2014
DOI: 10.1590/s0102-86502014001800010
|View full text |Cite
|
Sign up to set email alerts
|

Association of lipophilic opioids and hyperbaric bupivacaine in spinal anesthesia for elective cesarean section. Randomized controlled study

Abstract: PURPOSE:To evaluate the efficacy and side-effects of fentanyl and sufentanil combined with hyperbaric spinal bupivacaine in elective cesarean section. METHODS:A prospective, randomized, double-blind study with 64 term parturients, distributed into 2 groups according to the opioid combined with hyperbaric bupivacaine 0.5% (10mg): GF -fentanyl (25µg) and GS -sufentanil (5.0µg). The latency and maximum sensory block level; degree and duration of motor block; duration and quality of analgesia; maternal-fetal reper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
(37 reference statements)
1
10
2
3
Order By: Relevance
“…Motiani et al ( 26 ) and Dourado et al ( 31 ) mentioned higher frequency of itching in sufentanil group than other groups. Although Braga et al ( 21 ) mentioned no significant difference in the incidence of itching between the 2 groups as well, itching was much more noted in sufentanil group, and this result was inconsistent with ours. This difference in the results might be noted as a result of lower dosage of administered sufentanil in our study (2.5 mcg) compared to others (5 - 7.5 mcg).…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Motiani et al ( 26 ) and Dourado et al ( 31 ) mentioned higher frequency of itching in sufentanil group than other groups. Although Braga et al ( 21 ) mentioned no significant difference in the incidence of itching between the 2 groups as well, itching was much more noted in sufentanil group, and this result was inconsistent with ours. This difference in the results might be noted as a result of lower dosage of administered sufentanil in our study (2.5 mcg) compared to others (5 - 7.5 mcg).…”
Section: Discussioncontrasting
confidence: 80%
“…Our study revealed that the use of fentanyl (25 mcg) and sufentanil (2.5 mcg) in combination with intrathecal bupivacaine was associated with more appropriate analgesia (312.5 minutes and 314 minutes, respectively) compared to 116 minutes by placebo during and after surgery. In a study by Braga et al ( 21 ), duration of analgesia in the fentanyl group was 177 minutes and it was 210 minutes in sufentanil group, and this difference might be noted as a result of lower dose of administered bupivacaine (10 mg). However, Saraswat et al ( 24 ) mentioned 322 and 409 minutes of analgesia by fentanyl and sufentanil groups, respectively.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Lipophilic opioids are used as adjuvants in central blockades. Fentanyl at a dose of 25 µg and sufentanil at a dose of 5 µg in combination with hyperbaric bupivacaine used for spinal anesthesia of caesarean section are characterized by comparable effectiveness, they are safe for the mother and the fetus, while the analgesic effect of sufentanil lasts longer [8]. Sufentanil has no negative effects on the fetus due to its binding to alpha1-glycoprotein at doses below 30 µg.…”
Section: Anaesthetic Drugsmentioning
confidence: 99%
“…This is consistent with the results of previous studies. 16 17 …”
Section: Discussionmentioning
confidence: 99%